User Satisfaction Analysis f Service Quality Of Dapodik Applications (Educational Data) Using Servqual Method - Rizki Novendra; Nizwardi Jalinus; Waskito Waskito; Afriansyah Afriansyah; Anna Rasfira (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Dapodik is an education data system with a national scale in which there are various kinds of information regarding educational data units. The problem that occurs is that the operator has difficulty if the input data is invalid, so to correct the invalid input data, it is done in the operator's account, while to synchronize the data the operator must first login to the principal's account. In addition, for filling the infrastructure (facilities and infrastructure) operators have difficulty measuring the percentage of damage that occurs to school facilities because they are not in their expertise or field. Therefore, this dapodik application needs to be measured user satisfaction with the quality of its services using the servqual method. This study aims to measure user satisfaction in using the dapodik application on the quality of its services using the servqual method. The results of the measurement can be concluded that the empathy dimension, H5 (-1.03) should be further improved because the value of user dissatisfaction is higher. In addition, based on tangible values, reliability, responsiveness and assurance are still not good, so it is necessary to improve the quality of dapodik application services.